Recruitment of LC3 by Campylobacter jejuni to Bacterial Invasion Site on Host Cells via the Rac1-Mediated Signaling Pathway - Fukushima, Shiho; Shimohata, Takaaki; Inoue, Yuri; Kido, Junko; Uebanso, Takashi; Mawatari, Kazuaki; Takahashi, Akira (Frontiers in Cellular and Infection Microbiology, 2022)
Campylobacter jejuni is a leading cause of food-borne disease worldwide. The pathogenicity of C. jejuni is closely associated with the internalization process in host epithelial cells, which is related to a host immune response. Autophagy indicates a key role in the host’s innate immune system to exclude invasive pathogens. Most bacteria are captured by autophagosomes and degraded by autophagosome-lysosome fusion in host cells. However, several pathogens, such as Salmonella and Shigella, avoid and/or escape autophagic degradation to establish infection. But autophagy involvement as a host immune response to C. jejuni infection has not been clarified. This study revealed autophagy association in C. jejuni infection. During infection, C. jejuni activated the Rho family small GTPase Rac1 signaling pathway, which modulates actin remodeling and promotes the internalization of this pathogen. In this study, we found the LC3 contribution to C. jejuni invasion signaling via the Rac1 signaling pathway. Interestingly, during C. jejuni invasion, LC3 was recruited to bacterial entry site depending on Rac1 GTPase activation just at the early step of the infection. C. jejuni infection induced LC3-II conversion, and autophagy induction facilitated C. jejuni internalization. Also, autophagy inhibition attenuated C. jejuni invasion step. Moreover, Rac1 recruited LC3 to the cellular membrane, activating the invasion of C. jejuni. Altogether, our findings provide insights into the new function of LC3 in bacterial invasion. We found the interaction between the Rho family small GTPase, Rac1, and autophagy-associated protein, LC3.